The Impact of Artificial Intelligence (AI) on Talent Acquisition in Human Resource Management - Yashshri Choudhari; Prajjwol Shrestha; Gyanendra Singh; Sunali Bindra (Australasian Accounting, Business and Finance Journal, 2025)
Accentuating its role in many industries, Artificial Intelligence (AI) has transformed Human Resource Management (HRM), particularly Talent Acquisition (TA). This paper focuses on the ways in which AI changes TA in HRM by improving work processes, diversifying the applicant pool, and improving recruitment success. Using a quantitative research approach, the study invites 204 respondents. It applies complex statistical methods, regression analysis, Correlation, T-tests, and ANOVA to determine to what extent the AI can revolutionise the talent acquisition process. The study provided support for the hypothesised relationships, suggesting that there are benefits in implementing AI, and that implementation triggers change in talent acquisition processes. Finally, this study contributes to knowledge that can be applied to further strategic developments for HR departments as they continue to undergo change and seek ways toward implementing better and equal recruitment processes.
Keywords: Artificial Intelligence; Talent Acquisition; Human Resource Management; AI Adoption; Diversity; Efficiency; Recruitment Outcomes; Predictive Analytics; Recruitment; AI-driven Tools; HR Efficiency; Managerial Attitudes; Innovation in HRM; Technology in Recruitment.